About the ‘interim’ or discovering the depths of the pre-Roman Iron Age - Michałowski, Andrzej; Teska, Milena; Krzyżanowska, Marta; Kaczmarska, Patrycja; Frankiewicz, Mateusz; Żółkiewski, Marek; Niedzielski, Przemysław (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
The pre-Roman Iron Age, i.e. the last five last centuries BC, is one of the most mysterious periods in Polish prehistory and constitutes an extremely interesting research issue, which help concentrate the studies on it, into a compact group of research problems. The studies on the pre-Roman Iron Age carried out by the group of researchers at the Faculty of Archaeology of the Adam Mickiewicz University are based on the research traditions of Poznań archaeology. The focal point of work in recent years has been settlement pottery, which is a mass source acquired during excavations whose potential has not yet been fully exploited. One way to better understand the possibilities that this type of mass material can bring has been exploitation of the potential of archaeometry. The ongoing studies on the problems of the pre-Roman Iron Age strive to detail and explain the processes and changes occurring at the time. They fit into the Poznań tradition of studies on this period, being a continuation of previous work undertaken on its intricate issues – empowering it and leading it out of the titular ‘interim’, placing it in the fully deserved centre of research interests.
Keywords: pre-Roman Iron Age; settlement pottery; archaeometry